Optimal Raw Material Planning To Minimize Out of Stock Costs Using The Material Requirement Planning Method - Rudy Setiawan; Siti Mundari (Telkom University, 2026)
UD. Podo Moro, a folding ironing board manufacturer in Surabaya, experienced recurring Out of Stock (OOS) conditions caused by fluctuating demand, long supplier lead times, and the absence of a structured raw material planning system. These conditions resulted in production delays, emergency purchasing activities, and increased operational costs. This study aims to optimize raw material planning and minimize inventory costs through the implementation of the Material Requirement Planning (MRP) method. Demand forecasting was conducted using three quantitative methods, namely Moving Average (MA), Weighted Moving Average (WMA), and Exponential Smoothing (ES). The selected forecasting results were then used to develop Aggregate Planning and a Master Production Schedule (MPS). Furthermore, MRP calculations were performed using three lot sizing techniques: Lot for Lot (LFL), Economic Order Quantity (EOQ), and Fixed Order Quantity (FOQ). The results indicate that the Moving Average (MA) method produced the most consistent forecasting accuracy based on Mean Absolute Deviation (MAD) values and tracking signal analysis. Among the evaluated lot sizing techniques, the EOQ method generated the lowest total inventory cost of Rp 346,275,216, compared to Rp 417,215,710 for LFL and Rp 488,289,859 for FOQ during the January–June 2026 planning period. The implementation of MRP proved capable of improving procurement scheduling, reducing inventory shortages, minimizing emergency purchasing activities, and enhancing operational efficiency. Therefore, the EOQ-based MRP approach is recommended as the most effective strategy for minimizing OOS costs at UD. Podo Moro.